Persons, moral worth, and embryos a critical analysis of pro-choice arguments - SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
Bioethicists have achieved sensus on two ideas pertaining to beginning of life issues: (1) persons are those beings capable of higher-order cognition, or self-consciousness, and (2) it is impermissible to kill only persons. As a consequence, a consensus is reached regarding the permissibility of both destroying human embryos for research purposes and abortion. The present collection aims to interact critically with this consensus. Authors address various aspects of this "orthodoxy". Issues discussed include: theories of personhood and in particular the role of thought experiments used in support of such theories; the notion of an intrinsic potential and the moral relevance of having one; new formulations of the virtue argument against abortion rights; four-dimensionalism and abortion; the notion of moral status and who (or what) has it; scientific accounts of what a human being is, as well as addressing empirical evidence of fetal consciousness; and analysis of the public policy implications given the epistemic status of pro-choice arguments. Given the issues discussed and that the arguments in critical focus are fairly new, the collection provides a novel, comprehensive, and rigorous analysis of contemporary pro-choice arguments
Introduction: What are Persons? What is Valuable? Stephen Napier art 1. Philosophical Considerations I was Once a Fetus: That is Why Abortion is Wrong Alexander Pruss Brain Life and the Argument from Potential: Affirming the Ontological Status of Human Embryos and Fetuses Jason T. Eberl and Brandon P. Brown The Human Being, a Person of Substance: A Response to Dean Stretton Francis J. Beckwith The Concept of Person in Bioethics Anselm Winfried Müller Abortion and Virtue Ethics Mathew Lu Embryos, Four-Dimensionalism, and Moral Status David Hershenov The Christian Hypothesis David W. Fagerberg Fetal Interests, Fetal Persons, and Human Goods Christopher Tollefsen Part II. Scientific Considerations Fetal Pains and Fetal Brains A.A. Howsepian A Biological Definition of the Human Embryo Maureen L. Condic Part III. Perspectives from Law and Political Philosophy Public Reason and Abortion Revisited David Thunder Sexual Markets and the Law Helen M. Alvaré Index
Includes bibliographical references and index
Electronic reproduction
Keywords: Abortion -- Moral and ethical aspects; Abortion -- Religious aspects